Low pregnancy associated plasma protein-a (PAPP-A) in the first trimester – is it a predictor of poor perinatal outcome?. (7th June 2011) - Karim, J; Sau, A; Percival, S
Abstract : Aim: To examine the predictive value of pregnancy associated plasma protein (PAPP-A) for various markers of poor pregnancy outcome. Method: Databases at University Hospital Lewisham were used retrospectively to identify all singleton pregnancies which underwent first trimester combined screening between July 2008 and April 2010 and who were found to have levels of PAPP-A≤0.4 MOM. The perinatal courses of these pregnancies (n=256) were evaluated for signs of adverse outcome (spontaneous abortion, stillbirth, preterm labour, intrauterine growth restriction (IUGR), early onset pre-eclampsia, late-onset pre-eclampsia, gestational hypertension and placental abruption) and were compared to the outcomes of a matched control group of pregnancies (n=277) with normal PAPP-A levels. Results: Women with low serum PAPP-A were 5.0 times more likely to suffer fetal loss than those in the control group with an increased incidence of spontaneous abortion (RR 1.7) and of stillbirth (RR 2.3). The overall relative risk of IUGR was 2.2. However, IUGR was 4.3 times more prevalent in pregnancies with PAPP-A≤0.2 than in pregnancies from the control group. Results indicated that women with low PAPP-A were also at increased risk of preterm birth (RR 1.9), early pre-eclampsia (RR 2.0), late pre-eclampsia (RR 1.9) and gestational hypertension (RR 1.3). There were no incidences of placental abruption in live birth pregnancies from either group. Conclusions: This study shows that serum PAPP-A is an important marker for poor pregnancy outcome and that women with low serum PAPP-A levels would benefit from increased monitoring of their pregnancies.